RARE ASSOCIATION OF DOWN SYNDROME WITH DANDY WALKER MALFORMATION - Goyal, Suresh; H., Vignesh Nayak; Meena, Reeta (Journal of Health and Allied Sciences NU, 2014)
We report on a patient with Down syndrome and a multi-systemic condition comprising congenital heart disease (ASD) and neurological malformation (Dandy walker malformation). The co-occurrence of Down syndrome (DS) and Dandy walker malformation is relatively uncommon
Keywords: Down syndrome; Dandy walker malformation